Infections in gynecology and obstetrics: The Peruvian Society of Obstetrics and Gynecology scientific production during its seventy years of institutional life - Alarcón-Villaverde, Jorge (2017)
Infections in gynecology and obstetrics are pathologies that affect women throughout their life; some of them represent public health problems. The Peruvian Society of Obstetrics and Gynecology, in its seventieth anniversary, since its foundation until today maintains a constant concern on this subject. Through the years it has promoted and published various investigations and reports by members of the Society and from the institutions where they labor. These are exposed in this article with special emphasis on historical, pioneering and relevant papers, and published in The Peruvian Journal of Gynecology and Obstetrics, the official scientific publication of the Society.